Discharge of treated Fukushima nuclear accident contaminated water: macroscopic and microscopic simulations. Issue 1 (26th November 2021) - Liu, Yi; Guo, Xue-Qing; Li, Sun-Wei; Zhang, Jian-Min; Hu, Zhen-Zhong
Abstract : The diffusion process of the treated Fukushima nuclear accident contaminated water to be discharged into the Pacific Ocean from 2023 is analyzed by two analysis models from macroscopic and microscopic perspectives. Results show that the tritium will spread to the whole North Pacific in 1200 days, which is important to formulate global coping strategies.